A relevância da trama estocástica na impressão offset. Desenho de estes aplicáveis no setor mobiliário - Colen, José (2015)
The latest technologies and printing methods bring into the graphic industry a higher and better printing production capacity along with unequivocal advantages to the final quality of the work produced. To be able to know up to what point the usage of the stochastic screen brings benefits to that quality and to what extent it is apprehended by the public user of the printed materials, could well be a drive to practices and procedures renewal in the sector, as well as a way of improving and adding value to the final printing product. In this study we ran offset printing tests in stochastic and conventional screen, so that they could be analyzed by professionals and general public alike, from a set of images, carefully selected, according to the desired area of study. The process here presented allows the validation of some more subjective or less evident questions regarding the printing industry market, making it possible to generate basis of new work models within the industry or in complementary areas, such as, for example, in the area of design services rendered or in the product conception.